Comparative study of two series of laparoscopic and open cholecystectomy performed by the same surgical team - Matteucci, Pablo; Geninazzi, Héctor; Praderi, Luis; Praderi (h), Luis; Balboa, Oscar; Tchekmedyian, Vartan; Voelker, Ricardo; Martell, Miguel (Cirugía del Uruguay, 1994)
The autors compared the results of two series of open and laparoscopic cholecistectomy, during same period of time. Laparocopic cholecistectomy showed more benefits than the open one. These patients were most confortable alter the operation, with less internation time and less complications.